2008
DOI: 10.1074/jbc.c800030200
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 Inhibits Nedd4 Ubiquitin E3 Activity and Enhances the Innate Antiviral Response*

Abstract: Interferons regulate diverse immune functions through the transcriptional activation of hundreds of genes involved in antiviral responses. The interferon-inducible ubiquitin-like protein ISG15 is expressed in cells in response to a variety of stress conditions like viral or bacterial infection and is present in its free form or is conjugated to cellular proteins. In addition, protein ubiquitination plays a regulatory role in the immune system. Many viruses modulate the ubiquitin (Ub) pathway to alter cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
167
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 27 publications
5
167
1
Order By: Relevance
“…All three forms could potentially affect HCV viral production. In other systems, the free form of ISG15 has been shown to inhibit the release of Ebola virus-like particles by interfering with the activity of Nedd4 (Malakhova & Zhang, 2008;Okumura et al, 2008). ISGylation is critical to the effect of ISG15 on Sindbis virus, and ISGylation is targeted by the human influenza virus NS1 protein (Yuan & Krug, 2001;Lenschow et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All three forms could potentially affect HCV viral production. In other systems, the free form of ISG15 has been shown to inhibit the release of Ebola virus-like particles by interfering with the activity of Nedd4 (Malakhova & Zhang, 2008;Okumura et al, 2008). ISGylation is critical to the effect of ISG15 on Sindbis virus, and ISGylation is targeted by the human influenza virus NS1 protein (Yuan & Krug, 2001;Lenschow et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4C. Protein ISGylation may interfere with the UPS function in multiple arms, such as the competition of E1/E2/E3s for ubiquitylation (50) and the competition of ubiquitylation sites on substrates (51). One particular effect may be through ISGylation of ubiquitylated proteins, which disrupts the formation of long ubiquitin chains (52).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the biological function of ISGylation has only been elucidated for some cellular target proteins. These include the functional inhibition of enzymes Takeuchi et al, 2006;Zou et al, 2007;Malakhova and Zhang, 2008) and the enhancement of the cap structure-binding activity of the translational suppressor, 4EHP (Okumura et al, 2007). Recent studies have shown that ISGylation negatively regulates the ubiquitin-proteasome pathway by direct interference with polyubiquitination (Desai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%